Perfil de risco imunológico e resposta humoral ao citomegalovírus e associação com o estado cognitivo funcional em idosos - Correa, Bruna Luz (2012)
Introduction: The immune risk phenotype (IRP), as shown by increased CD8+ and low CD4+ T cell counts, and cognitive impairment have been associated with increased morbidity and mortality in very old subjects. Recent evidence suggests that persistent viral infections of the herpesviridae family such as cytomegalovirus (CMV) are likely to be involved with these specific T cell changes. This study aims to identify the IRP and investigate possible associations with viral infections, cognitive and functional states of elderly in Brazil. Material and Methods: 360 elders aged between 60-103 years were recruited from the public health care system in Porto Alegre, Brazil. Peripheral blood was collected and lymphocyte subsets (CD4+, CD8+, NK, NK T, B and CD8+CD28-) assessed by multi-color flow cytometry. CMV and Epstein-Barr virus (EBV) serologies were determined by ELISAs. Cognitive function was evaluated by the word list memory and constructional praxis from the standard neuropsychological battery of Consortium to Establish a Registry for Alzheimer s Disease and Mini Mental Status Examination (MMSE) inventory. PFEFFER Functional Activities Questionnaire was used to determine activities of daily living. Results: 59 individuals were defined with IRP (CD4/CD8 ratio < 1). Increased IgG titers to CMV (p<0.01) but not to EBV were found in the IRP+ group as compared to non-IRP. The IRP+ elders had a greater late-memory deficit (p<0.05) and more functional disability and dependency (p=0.01) when compared with the non-IRP group. Subjects with both IRP and cognitive impairment did not show synergist effects upon lymphocytes or viral serologies. Conclusions: The IRP was identified in 16% of the Brazilian community dwellers. Our data further indicate the association of CMV with IRP and both cognitive and functional disability/dependency during aging.